Secondary Effects of Radiation Therapy to the Hand for Benign Conditions. (May 2020) - Steen, Kalila; Hayward, Victoria; Novak, Christine; Anastakis, Dimitri; McCabe, Steven
Background: Emerging literature introduces radiation therapy for benign hand conditions. However, hand surgeons are wary recommending radiation therapy for nonmalignant conditions. In our practice, we have used radiation therapy for patients who present with infiltrative or recurrent giant cell tumor of the tendon sheath (GCTTS) since 1998. The purpose of this study is to examine the secondary effects of radiation to the hand through the critical lens of a hand surgeon.Methods: A case series of patients who received radiation therapy for GCTTS were reviewed. The Radiation Oncology/Toxicity Grading Late Radiation Morbidity Scoring Schema was used, and patients were questioned about symptoms and examined for physical findings involving their irradiated digits.Results: A total of 8 patients with GCTTS presented for follow-up. The average patient age was 59.1 years, and the average time since radiation therapy was 5.4 years. Patients had an average of 2.3 surgeries on the affected digit prior to receiving radiation therapy. The average Disabilities of the Arm, Shoulder, and Hand score was 8.1. The most common sign of radiation was nail changes. All patients complained of sensibility changes, although only 2 of the 8 patients had abnormal moving 2-point discrimination tests. There were no confirmed recurrences of GCTTS and no skin cancers.Conclusions: Patients who received radiation therapy to the hand report high levels of satisfaction with the therapy. Radiation therapy is tolerated well by these patients and has a low level of morbidity in our population.